Optimization of UV-C Processing of Donkey Milk: An Alternative to Pasteurization? - Papademas, Photis; Mousikos, Panagiotis; Aspri, Maria (My University, 2021)
The effect of UV-C light technology on the inactivation of six foodborne pathogens inoculated in raw donkey milk was evaluated. Fresh raw donkey milk was artificially inoculated with the following foodborne pathogens-L. inoccua (NCTC 11288), S. aureus (NCTC 6571), B. cereus (NCTC 7464), Cronobacter sakazakii (NCTC 11467), E. coli (NCTC 9001), Salmonella enteritidis (NCTC 6676)-and then treated with UV-C doses of up to 1300 J/L. L. innocua was the most UV-C-resistant of the bacteria tested, requiring 1100 J/L for complete inactivation, while the rest of the bacteria tested was destructed in the range of 200-600 J/L. Results obtained from this study indicate that UV-C light technology has the potential to be used as a non-thermal processing method for the reduction of spoilage bacteria and foodborne pathogens that can be present in raw donkey milk.
Keywords: UV-C technology; Donkey milk; Microbial inactivation; Milk pathogens; Non-thermal methods